1994
DOI: 10.1111/j.1365-2958.1994.tb01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein H — a surface protein of Streptococcus pyogenes with separate binding sites for lgG and albumin

Abstract: Protein H, a molecule expressed at the surface of some strains of Streptococcus pyogenes, has affinity for the constant (IgGFc) region of immunoglobulin (Ig) G. In absorption experiments with human plasma, protein H-sepharose could absorb not only IgG but also albumin from plasma. The affinity constant for the reaction between albumin and protein H was 7.8 x 10(9) M-1, which is higher than the affinity between IgG and protein H (Ka = 1.6 x 10(9) M-1). Fragments of protein H were generated with deletion plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 54 publications
3
83
0
1
Order By: Relevance
“…From the data shown in Table 1, it can be concluded that the association (K A ) and dissociation (K D ) constants are in the range of 10 7 and 10 Ϫ8 , respectively, which confirms a specific interaction of SOF75 with fibronectin. However, the binding strength is 1 order of magnitude lower, as described for other relevant MSCRAMMs of gram-positive cocci and their binding to human matrix proteins (2,14,21,28,37,49). It is possible that SOF is important for establishment of initial low-strength contact between the GAS and fibronectin, prior to high-affinity binding of SfbI or PrtF2 in SfbI-negative strains (28).…”
mentioning
confidence: 87%
“…From the data shown in Table 1, it can be concluded that the association (K A ) and dissociation (K D ) constants are in the range of 10 7 and 10 Ϫ8 , respectively, which confirms a specific interaction of SOF75 with fibronectin. However, the binding strength is 1 order of magnitude lower, as described for other relevant MSCRAMMs of gram-positive cocci and their binding to human matrix proteins (2,14,21,28,37,49). It is possible that SOF is important for establishment of initial low-strength contact between the GAS and fibronectin, prior to high-affinity binding of SfbI or PrtF2 in SfbI-negative strains (28).…”
mentioning
confidence: 87%
“…Like the GA modules the C repeats comprise about 40 amino acid residues, but these HSA-binding units show no sequence homology. Nevertheless, they compete for the same binding site in HSA [36]. These observations indicate that HSAbinding in Gram-positive bacteria has evolved convergently which, in turn, suggests that the ability of binding this abundant plasma protein adds selective advantages to the bacteria.…”
Section: Discussionmentioning
confidence: 78%
“…Similar binding properties do not imply structural similarity. For instance, the Igbinding domains of staphylococcal protein A and streptococcal protein G show no sequence homology and have very different global folds, but still bind to overlapping sites in IgG [36,37]. Neither does structural similarity imply similar binding characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эффект повышения концен-трации IgG наблюдается и у пациентов с острыми стрептококковыми инфекциями. Помимо IgG, белки М семейства могут связывать и другие белки плазмы крови: фибронектин, фибриноген, плаз-миноген, альбумин, IgA и компоненты компле-мента [16,19,21]. Взаимодействие стрептококков с таким широким кругом белков крови не может пройти для организма-хозяина бесследно.…”
Section: Introductionunclassified